Environmental Collapse and the Anti-Capitalist Potentialities of the Environmental Struggle - Novaes, Henrique Tahan (Pontifícia Universidade Católica de São Paulo, 2020)
This article seeks to analyze the environmental question from a Marxist perspective. We draw on studies by Marxists that discuss the advance of transnational corporations and how these are producing environmental collapse. Then we attempt to demonstrate the anti-capitalist potential of the environmental struggle, as well as the risks of this movement “parking” in a kind of “eco-capitalism.”